Counter terrorism in diverse communities - Ekici, Siddik (NATO science for peace and security series. E, Human and societal dynamics, 2011)
Many affluent societies around the world are proving an increasingly attractive destination for immigrants who are culturally and linguistically different. This can present challenges to state and local authorities attempting to identify those who pose a terrorist threat. There is a need to understand whether diversity in our communities poses a threat and, since diversity cannot be avoided, how it can be successfully incorporated into countering possible terror related threats. This book presents papers from the NATO Advanced Research Workshop (ARW) held in Antalya, Turkey, in May 2011. The purpose of the workshop was to explore how culturally and linguistically diverse communities can most effectively respond to the threat of terrorism. With participants consisting of academics, researchers, law enforcement professionals and terrorism/civil society consultants from 17 different countries, the book ties together research and thoughts focusing on the causes and complexity of terrorism; counterterrorist strategies and approaches, as well as the relationship between diversity and terrorist incidents. Following a general introduction to counterterrorism and diversity, the book is divided into four sections: the terrorism problem; the prevention of terrorism; community oriented counterterrorism and finally, case studies. With contributions from an outstanding group of international participants addressing this important global issue, the book will be of value to anyone with an interest in countering the terrorist threat.